THE INFLUENCE OF MASS MEDIA ON LEARNERS’ LANGUAGE DEVELOPMENT - Umirzokova Oynisa Zokirovna (International Engineering Journal For Research & Development, 2022)
Different types of Mass Media have end up a fact of life, and it's far rational to make use of them handiest as a supportive device for teaching young children. This article aims to clarify the significance of Mass Media in language development, its role in learning foreign languages, the beneficial sides of different media types in language learning process and also the sensible influence of media types on language development in terms of vocabulary, listening, speaking, comprehension skills. This article also clarifies the usage of media for children’ social, educational developments in interaction with adults.